Comparison of Postoperative Short-Term Outcomes between Tension-Free Vaginal Mesh Surgery Using the Capio™ SLIM Suture Capturing Device and Conventional TVM Surgery for Pelvic Organ Prolapse - Haruhiko Kanasaki; Aki Oride; Tomomi Hara; Satoru Kyo (Obstetrics and Gynecology International)
Aim. We compared the short-term effectiveness of tension-free vaginal mesh (TVM) surgery using the Capio SLIM suture capturing device and conventional TVM surgery for treatment of pelvic organ prolapse. Methods. We retrospectively compared postoperative pain, urinary function, and length of hospital stay between 7 patients who underwent TVM surgery using the Capio device and 9 patients who underwent conventional TVM surgery. Results. There was no significant between-group difference in mean age between the Capio TVM group and the conventional TVM group (76.0 ± 5.6 years and 72.5 ± 11.5 years) or in mean operating time (86.56 ± 23.33 min and 95.28 ± 23.88 min). Four of the 7 patients in the Capio TVM group could not sense the urge to urinate after removal of the urethral catheter, but all patients in the conventional TVM group did so. The volume of the first voluntary urination was significantly smaller in the Capio TVM group than that in the conventional TVM group (102.14 ± 80.57 mL versus 472.22 ± 459.43 mL). The mean residual urine volume after the first voluntary urination was greater in the Capio TVM group than that in the conventional TVM group (285.70 ± 233.82 mL versus 34.56 ± 73.31 mL). The number of catheter days and mean maximal volume of residual urine were significantly greater in the Capio TVM group. The mean postoperative hospital stay was 6.57 ± 1.83 days in the Capio TVM group and 3.2 ± 0.42 days in the conventional TVM group. Six patients who underwent Capio TVM surgery complained of deep-seated pain in the hip region. Conclusion. Urinary function may worsen postoperatively when the Capio TVM device is used in patients with pelvic organ prolapse.